Measuring. Monitoring. Management. Control - A.J. Alieva; Kh.S. Alieva; M.G. Ashrafov; N.Kh. Mustafazade (Измерение, мониторинг, управление, контроль)
Background. The albedo of the earth's surface is an important indicator that determines the energy balance that exists between our planet and the atmosphere. The issues of optimization of albedometric measurements carried out by spectrometric equipment installed on board an unmanned aerial vehicle (UAV) are considered. The aim of the work is to solve the problem of optimizing albedometric measurements, taking into account the logarithmic relationship between the raw primary digital readings (DN) and the real indicator of reflection of natural and artificial terrestrial objects in the red, green and blue spectral ranges. The object of the study is albedometric measurements carried out by UAVs. The subject of the study is the optimization of albedometric measurements in narrow spectral ranges. Materials and methods. Using the variational method, the optimal dependence of the reflection index of terrestrial objects on the zenith angle of the UAV position relative to the object under study is investigated. The optimization criterion is the target functional in the form of an integrated value DN over the entire range of the change in the specified zenith angle. In the optimal mode, this functionality should reach its maximum if some restrictive condition is imposed on the specified dependence. Results. Using the variational optimization method, the optimal type of the specified dependence is calculated. It is shown that the results of the optimization are indirectly confirmed by the data of well-known experimental studies. Conclusion. Choosing the optimal ratio between the specified zenith angle and the reflection index of objects makes it possible to increase the efficiency of using UAVs for search purposes.